Antepartum Causes of Cerebral Palsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
Six neonates with destructive brain lesions of fetal onset, diagnosed by radiological and neurophysiological studies, are reported from the Departments of Pediatrics, Neurology, Radiology, and Obstetrics and Gynecology, Magee-Womens Hospital, Pittsburgh, PA and Children's Hospital of Pittsburgh.